Effect of the formulation on the quality of gluten-free bread with unripe plantain and Brosimum alicastrum - Fernández-Martínez, Lizbeth Alejandra; Sauri-Duch, Enrique; Ríos-Soberanis, Carlos Rolando; Lizama-Uc, Gabriel; Trejo-Valencia, Radamés; Moo-Huchin, Victor Manuel (Ecosistemas y Recursos Agropecuarios, 2024)
The objective of this study was to evaluate different levels of ingredients and mixing times to elaborate gluten-free bread with good physical quality. The gluten-free bread was processed with flour composed of unripe plantain and B. alicastrum with different levels of water (between 80 and 115 mL), transglutaminase enzyme (between 0.10 and 1.5%), pumpkin protein concentrate (between 1.0 and 10.0%) and mixing time (between 1.0 and 10 min). It was found that varying the level of each ingredient and the mixing time has a significant effect on the specific volume, the percentage of alveoli area and the alveolar density. Bread with good physical quality (specific volume 1.62 cm3 g-1, 1.40 alveoli mm-2 and 23.98% alveolar area) was obtained from 115 mL of water, 0.5% enzyme, 2% protein concentrate and a time of 3 min mixing.
Keywords: crumb; protein concentrate; pumpkin; gluten-free flour; transglutaminase